2019
DOI: 10.1136/jmedgenet-2018-105792
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of germline pathogenic BRCA1/2 variants in sequential epithelial ovarian cancer cases

Abstract: IntroductionPoly(ADP-ribose) polymerase inhibitors significantly improve progression-free survival in platinum-sensitive high-grade serous and endometrioid ovarian carcinoma, with greatest benefits observed in women with a pathogenic BRCA1/2 variant. Consequently, the demand for germline BRCA1/2 testing in ovarian cancer has increased substantially, leading to the screening of unselected populations of patients. We aimed to determine the prevalence of pathogenic germline BRCA1/2 variants in women diagnosed wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 46 publications
1
15
0
Order By: Relevance
“…Almost all patients included in this study were also tested for BRCA1 and BRCA2 somatic and germline variants using a clinically validated method [ 16 ], and this study was able to identify all 15 patients known to be carriers of deleterious BRCA1/BRCA2 germline variants, which allowed validation of the custom panel we designed for those genes. The frequency of pathogenic BRCA1 and BRCA2 germline variants in this unselected series of OC patients was 13.7%, which is in concordance with previous studies that reported frequencies between 13% and 18% [ 12 , 16 , 19 , 20 , 21 ]. Furthermore, BRCA1 / BRCA2 tumor sequencing allows the detection of both germline and somatic variants in a single test, the latter having a frequency ranging from 4% to 7% [ 16 , 22 , 23 ].…”
Section: Discussionsupporting
confidence: 92%
“…Almost all patients included in this study were also tested for BRCA1 and BRCA2 somatic and germline variants using a clinically validated method [ 16 ], and this study was able to identify all 15 patients known to be carriers of deleterious BRCA1/BRCA2 germline variants, which allowed validation of the custom panel we designed for those genes. The frequency of pathogenic BRCA1 and BRCA2 germline variants in this unselected series of OC patients was 13.7%, which is in concordance with previous studies that reported frequencies between 13% and 18% [ 12 , 16 , 19 , 20 , 21 ]. Furthermore, BRCA1 / BRCA2 tumor sequencing allows the detection of both germline and somatic variants in a single test, the latter having a frequency ranging from 4% to 7% [ 16 , 22 , 23 ].…”
Section: Discussionsupporting
confidence: 92%
“…BRCA1 mutations dominated in patients <60 years over BRCA2 mutations, while in patients ≥ 60 years, their frequencies were comparable. Moreover, we revealed 29 BRCA1/2 mutation carriers (13.9% of patients) in 208 OC patients diagnosed at ≥60 years with no family cancer history, while Morgan and colleagues detected only two (4.3%) BRCA1/2 mutations in 46 sporadic OC patients ≥ 60 years [33]. Even in the oldest subgroup of our OC patients diagnosed at ≥70 years, the frequency of BRCA1/2 mutation carriers exceeded 18%, while in other studies, BRCA1/2 mutations' frequency in this age category was below 10% [34,35].…”
Section: Discussionmentioning
confidence: 61%
“…This likely reflects the increased penetrance of BRCA1 as compared with BRCA2 despite BRCA2 alterations being more common in the population as exemplified by gnomAD data [gnomAD v2.1.1 accessed 15th February 2021 BRCA1 loss of function (LoF), n = 141; BRCA2 LoF, n = 248], control frequencies from the BRIDGES study [ 23 ] and a recent population study in the USA [ 18 ]. Germline BRCA1 variants are often associated with young-onset life-limiting grade 3 triple-negative breast cancers [ 24 ], whereas for women ≥60 years with no previous cancer history who develop an epithelial ovarian cancer, BRCA2 variants are more frequently detected [ 25 ].…”
Section: Discussionmentioning
confidence: 99%